Avaliação da política pública do contraturno: impactos na aprendizagem dos estudantes da EMEIEF Napoleão Bonaparte Viana - Cid, Maria Eliene Pereira Lima (2024)
The idea of full-time education emerges as a long-term alternative to face current educational challenges. However, this type of teaching still faces challenges in the national territory, including the need for adequate infrastructure, training of specialized teachers, development of integrated curricula and articulation with public policies that guarantee its effective and sustainable implementation. From this perspective, the present study addresses the importance of full-time education in the Brazilian context, highlighting the contribution of educators such as Anísio Teixeira (2002, 1977), Jaqueline Moll (2002, 2007, 2014), and Gadotti (2009). Its objective, therefore, is to evaluate the impact of public policy on after-school hours on the learning of students at EMEIEF Napoleão Bonaparte Viana, located in the municipality of Maracanaú – CE. The methodology adopted is qualitative, with a case study based on the narratives of different individuals included in the process. It was found that the After Hours Policy at Escola Napoleão Bonaparte Viana has contributed to improving student learning. However, there are areas that require improvements to ensure the effectiveness of the public policy evaluated. These aspects involve sociological, political and economic issues, where the prevalence of a market culture in contemporary society should not reinforce a competitive mentality to the detriment of values such as solidarity, collaboration and critical thinking.